Crenne, Hélisenne de ([1541] 2023). Les quatre premiers livres des Eneydes du treselegant poete Virgile, Traduictz de Latin en prose Francoyse, par ma dame Helisenne (Kriterium, 2024)
A 16th Century French Version of Virgil’s Aeneid In 1541, the author and translator known under the name Hélisenne de Crenne published her fourth and last work, a prose adaptation of the first four books of Virgil’s epos the Aeneid. The work was printed by Denys Janot and dedicated to king Francis I. The themes of Crenne’s Aeneid are in many ways similar to the themes present in her earlier works, works of which she was the original author. Crenne shows a vivid interest in love and its consequences in all her works ; moreover, she has a sharp focus on feelings. All this becomes crystal clear in her adaptation of Virgil ; a work which we consider as the keystone to her whole production. It seems that Crenne tried to make Virgil's work accessible and interesting to a broad audience through her adaptations of Virgil. Nonetheless, in contrast to her earlier works, her version of the Aeneid did not meet with any success among its contemporaries. The present volume is the first edition of the whole text since the first edition appeared. Besides Crenne’s Aeneid, this volume contains an extensive introduction where the work is presented : Crenne’s authorship ; translation in the 16th century ; Crenne’s technique and style ; the three extant copies of the printed edition ; her purposes with the edition. Moreover, our volume contains a commentary where each chapter is compared with the texts of Virgil and of Octovien de Saint-Gelais, the earlier French translator who inspired Crenne the most. Finally, there is a glossary. We have also reproduced the woodcuts from the original edition and tried to recreate a similar layout.